2020
DOI: 10.1002/ijgo.13324
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dietary pattern in early pregnancy using the FIGO Nutrition Checklist compared to a food frequency questionnaire

Abstract: Objective To evaluate the reliability and utility of the FIGO Nutrition Checklist to identify dietary and nutritional inadequacy in early pregnancy by comparing it against nutritional indicators and dietary quality indices (Dietary Approaches to Stop Hypertension [DASH] score, Mediterranean Diet Score [MDS], and Dietary Quality Index‐International [DQI‐I]), derived by a locally validated food frequency questionnaire (FFQ). Methods A prospective cohort study of healthy Chinese pregnant women randomly recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…The FIGO nutrition checklist is validated for use in pregnancy (114) . In a study with 156 healthy pregnant women, Tsoi et al found that the dietary information in the checklist correlated with the same data collected by a validated food frequency questionnaire.…”
Section: The Figo Nutrition Checklistmentioning
confidence: 99%
See 4 more Smart Citations
“…The FIGO nutrition checklist is validated for use in pregnancy (114) . In a study with 156 healthy pregnant women, Tsoi et al found that the dietary information in the checklist correlated with the same data collected by a validated food frequency questionnaire.…”
Section: The Figo Nutrition Checklistmentioning
confidence: 99%
“…The FIGO nutrition checklist is validated for use in pregnancy (114) . In a study with 156 healthy pregnant women, Tsoi et al .…”
Section: The Figo Nutrition Checklistmentioning
confidence: 99%
See 3 more Smart Citations